The mechanism and therapeutic potential of SIRT3 in central nervous system diseases: a review - Hong, Chuanbin; Wei, Yupeng; Wang, Yuchen; Lv, Guangfu; Dong, Xinglu; Huang, Xiaowei (Frontiers in Pharmacology, 2025)
Sirtuin-3 (SIRT3) is a mitochondrial deacetylase highly expressed in the nervous system, known to regulate mitochondrial homeostasis, energy metabolism, neuroinflammation, apoptosis, and oxidative stress, suggesting its potential neuroprotective role in central nervous system (CNS) disorders. Recent studies indicated that SIRT3 improves neuronal survival by reducing oxidative damage, alleviating neuroinflammation, and modulating autophagy. Therefore, it is imperative to conduct more in-depth and extensive investigations into the mechanisms underlying SIRT3 in central nervous system disorders. This review summarized current research advances on SIRT3, including its fundamental molecular structure, key downstream targets, and mechanisms of action in certain CNS diseases. It further analyzed the potential pharmacological mechanisms of several SIRT3 agonists and explored their therapeutic value in improving CNS disorders. Based on existing evidence, SIRT3 emerges as a promising therapeutic target, offering novel strategies for treating neurological diseases.